Unique Noncontact Monitoring of Human Respiration and Sweat Evaporation Using a CsPb2Br5-Based Sensor - Cho, Myung Yeon; Kim, Ik Soo; Kim, Seok Hun; Park, Chulhwan; Kim, Nam Young; Kim, Sang Wook; Kim, Sunghoon; Oh, Jong Min (ACS Applied Materials and Interfaces, 2021)
Respiration monitoring and human sweat sensing have promising application prospects in personal healthcare data collection, disease diagnostics, and the effective prevention of human-to-human transmission of fatal viruses. Here, we have introduced a unique respiration monitoring and touchless sensing system based on a CsPb2Br5/BaTiO3 humidity-sensing layer operated by water-induced interfacial polarization and prepared using a facile aerosol deposition process. Based on the relationship between sensing ability and layer thickness, the sensing device with a 1.0 μm thick layer was found to exhibit optimal sensing performance, a result of its ideal microstructure. This sensor also exhibits the highest electrical signal variation at 0.5 kHz due to a substantial polarizability difference between high and low humidity. As a result, the CsPb2Br5/BaTiO3 sensing device shows the best signal variation of all types of breath-monitoring devices reported to date when used to monitor sudden changes in respiratory rates in diverse situations. Furthermore, the sensor can effectively detect sweat evaporation when placed 1 cm from the skin, including subtle changes in capacitance caused by finger area and motion, skin moisture, and contact time. This ultrasensitive sensor, with its fast response, provides a potential new sensing platform for the long-term daily monitoring of respiration and sweat evaporation.
Keywords: Aerosol deposition process; Application prospect; Human-to-human transmission; Interfacial polarization; Non-contact monitoring; Personal health care; Respiration monitoring; Ultrasensitive sensors; Barium Compounds; Biosensing Techniques; Breath Tests; Bromine Compounds; Cesium; Equipment Design; Humans; Humidity; Lead; Monitoring, Physiologic; Nanocomposites; Respiration; Sweat; Titanium; aerosol deposition; CsPb2Br5/BaTiO3nanocomposite; interfacial polarization; respiration monitoring; sweat evaporation